Ethics as First Philosophy and its Implications for Psychotherapists and Counsellors (Existential Analysis: Journal of the Society for Existential Analysis, 2008)
In his essay Ethics as First Philosophy (1984) Emmanuel Levinas attempts to show through his analysis of non-intentional consciousness and its relationship with intentional consciousness how this relationship has striking similarities with our relationship with the Other: and how both of these relationships make us first and foremost ethical beings. In the first part of this paper I have attempted to guide the reader through Levinas' analysis that leads to his conclusion that we are ethical beings prior to any other concern. In the second part I have considered critically the implications of the analysis and conclusions of Levinas for therapists and therapy. I have also offered a personal exploration of my own experience of non-intentional consciousness and awareness of the other person.
Keywords: Knowledge; wisdom; intentionality; non-intentional consciousness; pre- reflective consciousness; consciousness; responsibility; justification; justice.